PENDAFTARAN TANAH DALAM HUKUM AGRARIA LAND REGISTRATION IN AGRARIAN LAW - Ita Surayya (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2022)
This study traces the shift in the legal configuration of land registration, namely the change in PP no. 10 of 1961 became PP No. 24 of 1997 concerning Land Registration by comparing the anatomy of the substance of the two government regulations. Researchers also criticize the development of regulations that encourage the acceleration of land registration in recent times. The researcher then conducted interviews with a number of agrarian activists to more deeply reveal the interests of legal ideology that caused a shift in the configuration of land registration. Changes from Government Regulation Number 10 of 1961 to Government Regulation Number 24 of 1997 concerning Land Registration are often understood only as technical changes to laws and regulations. In fact, law is not born from a vacuum so that it cannot be separated from its socio-historical context. Land registration is not only an administrative matter, but is filled with ideological-legal interests. The shift in the configuration of land registration is determined by the ideological-legal basis. In the early days of the birth of the LoGA, land registration was utilized as a land reform instrument to ensure that lands that exceeded the boundaries became objects of land redistribution. The implementation of this agrarian reform then foundered along with the change in the direction of legal ideology which was more capitalist in character so that the function of land registration turned into a land market instrument.